2017
DOI: 10.29356/jmcs.v61i1.126
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Biological Evaluation of New 3,4-diarylmaleimides as Enhancers (modulators) of Doxorubicin Cytotoxic Activity on Cultured Tumor Cells from a Real Case of Breast Cancer

Abstract: <p>A series of new 3,4-diarylmaleimides were synthesized in an optimized and efficient lineal sequence of three steps, starting from commercial maleimide. The biological evaluation of these compounds as enhancers (activity modulators) in the co-administration with doxorubicin treatment in breast cancer cells directly obtained from a patient, were essayed. The cancerous tissue BT026-512N was provided by the National Institute of Cancerology (INCAN) of México. This tissue was obtained by biopsy from a pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 10 publications
(15 reference statements)
0
11
0
Order By: Relevance
“…Chemotherapy raises the risk of blood clots such as deep-vein thrombosis because breast cancer patients are predisposed to blood clots. As a result, developing new heterocyclic compounds with fewer side effects to combat breast cancer remains a challenge for researchers [39,40]. Some reports showed that maleimide derivatives and succinimide derivatives exhibited promising structures for developing new agents as anticancer agents with merit investigation [41][42][43][44].…”
Section: Cytotoxicity Evaluationmentioning
confidence: 99%
“…Chemotherapy raises the risk of blood clots such as deep-vein thrombosis because breast cancer patients are predisposed to blood clots. As a result, developing new heterocyclic compounds with fewer side effects to combat breast cancer remains a challenge for researchers [39,40]. Some reports showed that maleimide derivatives and succinimide derivatives exhibited promising structures for developing new agents as anticancer agents with merit investigation [41][42][43][44].…”
Section: Cytotoxicity Evaluationmentioning
confidence: 99%
“…The chlorination protocol tolerated N-tosyl anilines containing electron-attracting (15)(16)(17)(18)(19) and electron-donating (20)(21)(22)(23) groups as well as di- (24) or tetra-substituted derivatives (25).…”
Section: Chlorination Of N-tosyl Anilinesmentioning
confidence: 99%
“…[7] In this REDOX process, the aromatic ring is oxidized and the external oxidant agent is reduced at the end of the transformation. It's worth highlighting the biological relevance by introducing inorganic groups such as halogens or nitro groups, since their presence on the aromatic rings it confers a wide range of activities such as anti-diabetic, [8][9][10] fungistatic, [11] antiinflammatory, [12,13] anti-nociceptive, [14][15][16][17][18][19] or as potential drugs in the cancer treatment, [20][21][22][23] or MDR-reversers [24] among others (Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…Science has as aim the discovery and understanding of nature to get knowledge for developing procedures which increase the quality of life in the planet as much as possible. In this sense, several discoveries for the treatment of highly relevant diseases of social relevance such as cancer, [1–4] diabetes [5] or AIDS [6] among the most relevant, have been the result of hard work over several years through the science. One of the most important tools which has played a key role in the development of the aforementioned treatments is organic synthesis .…”
Section: Introductionmentioning
confidence: 99%